The Internal Aspect of Social Rules. (19th August 2014) - Perry, Adam
Abstract : For a rule to exist in a society, its members must hold a certain attitude. It has proven difficult to identify that attitude, however. Here, I draw on recent work in the philosophy of action to show that the attitude we are looking for is 'acceptance' that the rule ought to be complied with, where this acceptance is held independent of any belief about the matter. One implication of this idea is that the attitude that underlies a social rule is analogous to a 'presumption' or 'fiction' about what ought to be done, as these terms are used in the law of evidence.